Exacerbation-like respiratory symptoms in individuals without chronic obstructive pulmonary disease: results from a population-based study. Issue 8 (4th April 2014) - Tan, W C; Bourbeau, J; Hernandez, P; Chapman, K R; Cowie, R; FitzGerald, J M; Marciniuk, D D; Maltais, F; Buist, A S; O'Donnell, D E; Sin, D D; Aaron, S D; et al.
Abstract : Rationale: Exacerbations of COPD are defined clinically by worsening of chronic respiratory symptoms. Chronic respiratory symptoms are common in the general population. There are no data on the frequency of exacerbation-like events in individuals without spirometric evidence of COPD. Aims: To determine the occurrence of 'exacerbation-like' events in individuals without airflow limitation, their associated risk factors, healthcare utilisation and social impacts. Method: We analysed the cross-sectional data from 5176 people aged 40 years and older who participated in a multisite, population-based study on lung health. The study cohort was stratified into spirometrically defined COPD (post-bronchodilator FEV1 /FVC < 0.7) and non-COPD (post bronchodilator FEV1 /FVC ≥ 0.7 and without self-reported doctor diagnosis of airway diseases) subgroups and then into those with and without respiratory 'exacerbation-like' events in the past year. Results: Individuals without COPD had half the frequency of 'exacerbation-like' events compared with those with COPD. In the non-COPD group, the independent associations with 'exacerbations' included female gender, presence of wheezing, the use of respiratory medications and self-perceived poor health. In the non-COPD group, those with exacerbations were more likely than those without exacerbations to have poorer health-related quality of life (12-item Short-Form Health Survey), miss social activities (58.5% vs 18.8%), miss work for income (41.5% vs 17.3%) and miss housework (55.6% vs 16.5%), p<0.01 to <0.0001. Conclusions: Events similar to exacerbations of COPD can occur in individuals without COPD or asthma and are associated with significant health and socioeconomic outcomes. They increase the respiratory burden in the community and may contribute to the false-positive diagnosis of asthma or COPD.